2003
DOI: 10.1309/lbrn-gf9m-jw2m-ht97
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Intussusception Associated With Adenovirus Infection in Mexican Children

Abstract: Formalin-fixed intestinal tissue specimens from 12 Mexican pediatric patients with intussusception were examined for the presence of adenovirus. Four patients (33%) had detectable adenovirus antigen in epithelial cells as determined by using immunohistochemical analysis. Two of the patients with positive immunohistochemical results had antigens in dendritic and mononuclear inflammatory cells, and 3 patients had positive results for species C adenovirus by in situ hybridization using adenovirus species-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
0
25
1
1
Order By: Relevance
“…Thus good bacteria can potentially control, or prevent the growth of pathogenic bacteria, in part via immune system development and metabolic processes and by mechanisms as yet not understood. 10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus good bacteria can potentially control, or prevent the growth of pathogenic bacteria, in part via immune system development and metabolic processes and by mechanisms as yet not understood. 10 .…”
mentioning
confidence: 99%
“…12 Multiple clinical and molecular factors are likely to determine gut colonization in early fetal life: bacterial characteristics such as number, diversity, cell surface antigens, the presence or absence of pili, host mucosal cell properties such as cell surface receptors, and epidemiologic factors such as gestational age, mode of delivery, exposure to maternal fecal flora, maternal diet, fetal antibiotic use, and type of infant feeding, including probiotics. 10, 12, 13 …”
mentioning
confidence: 99%
“…Of these, respiratory adenoviruses have created the greatest interest as they have been found in intestinal and mesenteric lymph node tissue, and in oropharyngeal and rectal cultures from affected children, and recently in a casecontrol series they were the only pathogens to be significantly associated with intussusception. 18,21,22 Despite the setback from the Rotashield experience, the Global Alliance for Vaccines and Immunizations declared rotavirus vaccine development is a priority. Several candidate vaccines are now under evaluation (including one derived from a Melbourne neonatal strain 23 ), although only two have reached phase III trials, with each enrolling more than 60 000 children from industrialized and developing countries.…”
mentioning
confidence: 99%
“…1,2 Previous studies have identified the role of infection in intussusception, 3,4 with adenovirus being the most common infectious association and Yersinia being the most common bacterial association. [5][6][7][8][9] Yersinia intussusception was first identified in 1976 and we have identified 32 reported cases world-wide to date (Table 1). [10][11][12][13][14][15][16][17][18][19][20][21][22] Yersinia are facultative Gram-negative anaerobes with global distribution.…”
Section: Introductionmentioning
confidence: 99%